2011
DOI: 10.1111/j.1539-6924.2011.01694.x
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Mortality Risk Reductions from Environmental, Transport, and Health Policies: A Global Meta‐Analysis of Stated Preference Studies

Abstract: We conduct, to our knowledge, the first global meta-analysis (MA) of stated preference (SP) surveys of mortality risk valuation. The surveys ask adults their willingness to pay (WTP) for small reductions in mortality risks, deriving estimates of the sample mean value of statistical life (VSL) for environmental, health, and transport policies. We explain the variation in VSL estimates by differences in the characteristics of the SP methodologies applied, the population affected, and the characteristics of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
204
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(218 citation statements)
references
References 96 publications
10
204
1
3
Order By: Relevance
“…First, using "cost-of-illness" techniques (23, 25), we calculated the direct health-care costs and the indirect costs of informal care and lost work days that are associated with deaths from specific diseases. Second, we used region-specific data on the willingness of individuals to pay for incremental mortality reductions, the "value of statistical life" (VSL) (21,22), to obtain an estimate of the cost of the lives (and life-years) saved under each dietary scenario. The two approaches span the range of potential valuation methods (33,34); the VSL approach is commonly used in cost-benefit analysis (22) to indicate societal preferences whereas the cost-of-illness approach, in particular its direct cost component, highlights the economic impact on the health-care sector and on patients (23,25).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, using "cost-of-illness" techniques (23, 25), we calculated the direct health-care costs and the indirect costs of informal care and lost work days that are associated with deaths from specific diseases. Second, we used region-specific data on the willingness of individuals to pay for incremental mortality reductions, the "value of statistical life" (VSL) (21,22), to obtain an estimate of the cost of the lives (and life-years) saved under each dietary scenario. The two approaches span the range of potential valuation methods (33,34); the VSL approach is commonly used in cost-benefit analysis (22) to indicate societal preferences whereas the cost-of-illness approach, in particular its direct cost component, highlights the economic impact on the health-care sector and on patients (23,25).…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, we would have used values that were specifically estimated for the regions used. However, such data do not exist for all of the regions included in this study, so instead we used a comprehensive and quality-screened database of VSL estimates (21,22) and a regional set of comparable CoI estimates (23)(24)(25). The valuation based on CoI estimates might be further improved by the inclusion of comorbidities that can affect the costs attributable to specific disease, and by breaking down aggregate cancer costs into site-specific costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are looking for factors that systematically affect the magnitude of the cancer VSL and VSCC within a cancer context, and we are not seeking to estimate the so-called cancer premium, which has been investigated, with mixed results, in earlier studies (Jones-Lee et al, 1985;Hammitt and Haninger, 2010;Adamowicz et al, 2011;Lindhjem et al, 2011;OECD, 2012). Moreover, in past research we have found that cancer values trump those for any other cause of death Ščasný, 2011, 2013) making it difficult to investigate issues of scope and attributes associated with illness and death.…”
Section: Approachmentioning
confidence: 99%